Associations Between Sleep Hygiene and Sleep Problems in Adolescents With ADHD: A Cross-Sectional Study. Issue 4 (February 2020) - Martin, Christina A.; Hiscock, Harriet; Rinehart, Nicole; Heussler, Helen S.; Hyde, Christian; Fuller-Tyszkiewicz, Matthew; McGillivray, Jane; Austin, David W.; Chalmers, Alexa; Sciberras, Emma
Objective: To determine whether self-reported sleep hygiene practices are associated with self- and parent-reported behavioral sleep problems in adolescents with ADHD.Method: Participants included 79 adolescents with ADHD (13-17 years) and their parents. Adolescents were asked to report on their sleep hygiene (Adolescent Sleep Hygiene Scale) and sleep (Adolescent Sleep Wake Scale). Parents also reported on their adolescent's sleep (Sleep Disturbance Scale for Children).Results: Poorer sleep hygiene was associated with higher total self-reported behavioral sleep problems and most self-reported sleep problems: falling asleep, reinitiating sleep, and returning to wakefulness. The association was also apparent for total parent-reported behavioral sleep problems, problems with initiating and maintaining sleep, and excessive somnolence.Conclusion: This study demonstrates small-to-moderate relationships between poor sleep hygiene practices and sleep problems in adolescents with ADHD, by both self- and parent-report.